Effects of Experimental Sleep Restriction on Weight Gain, Caloric Intake, and Meal Timing in Healthy Adults - Spaeth, Andrea M. (Associated Professional Sleep Societies, LLC, 2013)
STUDY OBJECTIVES: Examine sleep restriction's effects on weight gain, daily caloric intake, and meal timing. DESIGN: Repeated-measures experiments assessing body weight at admittance and discharge in all subjects (N = 225) and caloric intake and meal timing across days following 2 baseline nights, 5 sleep restriction nights and 2 recovery nights or across days following control condition nights in a subset of subjects (n = 37). SETTING: Controlled laboratory environment. PARTICIPANTS: Two hundred twenty-five healthy adults aged 22-50 y (n = 198 sleep-restricted subjects; n = 31 with caloric intake data; n = 27 control subjects; n = 6 with caloric intake data). INTERVENTIONS: Approximately 8-to-1 randomization to an experimental condition (including five consecutive nights of 4 h time in bed [TIB]/night, 04:00-08:00) or to a control condition (all nights 10 h TIB/night, 22:00-08:00). MEASUREMENTS AND RESULTS: Sleep-restricted subjects gained more weight (0.97 ± 1.4 kg) than control subjects (0.11 ± 1.9 kg; d = 0.51, P = 0.007). Among sleep-restricted subjects, African Americans gained more weight than Caucasians (d = 0.37, P = 0.003) and males gained more weight than females (d = 0.38, P = 0.004). Sleep-restricted subjects consumed extra calories (130.0 ± 43.0% of daily caloric requirement) during days with a delayed bedtime (04:00) compared with control subjects who did not consume extra calories (100.6 ± 11.4%; d = 0.94, P = 0.003) during corresponding days. In sleep-restricted subjects, increased daily caloric intake was due to more meals and the consumption of 552.9 ± 265.8 additional calories between 22:00-03:59. The percentage of calories derived from fat was greater during late-night hours (22:00-03:59, 33.0 ± 0.08%) compared to daytime (08:00-14:59, 28.2 ± 0.05%) and evening hours (15:00-21:59, 29.4 ± 0.06%; Ps < 0.05). CONCLUSIONS: In the largest, most diverse healthy sample studied to date under controlled laboratory conditions, sleep restriction promoted weight gain. Chronically sleep-restricted adults with late bedtimes may be more susceptible to weight gain due to greater daily caloric intake and the consumption of calories during late-night hours. CITATION: Spaeth AM; Dinges DF; Goel N. Effects of experimental sleep restriction on weight gain, caloric intake, and meal timing in healthy adults. SLEEP 2013;36(7):981-990.